The Video Nasties / Freedom and Censorship in the Media - Barker Martin (Pluto Press, 1984)
Introduction, Nasty Politics of Video Nasties?, Figuring Out the Arguments, Exactly What we Wanted, Falling Standards: A Short and Sharp History of Moral Decline, ''Nasties'': A Problem of Identification, Notes, Notes on Contributors.
Introduction, Nasty Politics of Video Nasties?, Figuring Out the Arguments, Exactly What we Wanted, Falling Standards: A Short and Sharp History of Moral Decline, ''Nasties'': A Problem of Identification, Notes, Notes on Contributors.